Odpowiedź:
10.
a)
4x - 3 = 3x + 5
4x - 3x = 5 + 3
x = 8
b)
5x + 2 = 7 - 3x
5x + 3x = 7 - 2
8x = 5 /:8
x = 5/8
c)
3(x - 1) = 0
3x - 3 = 0
3x = 3 /:3
x = 1
d)
-6(x + 1) = 24
-6x - 6 = 24
-6x = 24 + 6 /:(-6)
x = 30/(-6) = -5
e)
-7(x - 2) = 3x - 1
-7x + 14 = 3x - 1
-7x - 3x = -1 - 14
-10x = -15 /:(-10)
x = 15/10 = 3/2 = 1 1/2
f)
4(x - 1) = 6(1 + x)
4x - 4 = 6 + 6x
4x - 6x = 6 + 4
-2x = 10 /:(-2)
x = 05
11.
a)
0,2x + 0,3 = -0,5
0,2x = -0,5 - 0,3 /:0,2
x = -0,8/0,2 = -4
b)
0,4 + 0,25x = -2
0,25x = -2 - 0,4 /:0,25
x = -2,4/0,25 = 9,6
c)
2,1 - 0,3x = 0,4x
-0,3x - 0,4x = -2,1
-0,7x = -2,1 /:(-0,7)
x = 3
d)
-1,5x - 3 = 0,2x + 6
-1,5x - 0,2x = 6 + 3
-1,7x = 9 /:(-1,7)
x = -9 : 1,7 = -9 : 17/10 = -9 * 10/17 = -90/17 = -5 5/17
Szczegółowe wyjaśnienie: